Bifidobacterial growth stimulation by oligosaccharides generated from olive tree pruning biomass. (1st August 2017) - Ruiz, Encarnación; Gullón, Beatriz; Moura, Patrícia; Carvalheiro, Florbela; Eibes, Gemma; Cara, Cristóbal; Castro, Eulogio
Highlights: Olive tree pruning biomass (OTPB) can be used for oligosaccharides (OS) production. OTPB OS of varied degree of polymerization promote the growth of bifidobacteria. Shorter OS support higher biomass formation, OS consumption and acids production. Bifidobacterial counts increase during OS incubation with a fecal inoculum. OTPB OS could be used as bioactive ingredients in the formulation of functional foods. Abstract: This work aims to evaluate the prebiotic potential of oligosaccharides (OS) obtained from autohydrolysis of olive tree pruning biomass (OTPB). Two selected fractions (F1 and F2) were characterized and used in in vitro fermentations by two Bifidobacterium spp. ( B. adolescentis and B. longum ) and one fecal inoculum. The fraction F1 presented a lower average degree of polymerization (DP) mainly with OS ranging from 3 to 6 DP, whereas the fraction F2 corresponded to a pool of unsubstituted and acetylated oligomers with DP between 4 and 19. In the fermentation by Bifidobacterium, F1 supported a higher biomass formation, OS consumption and organic acids production than F2. With the fecal inoculum, the accumulation of organic acids, as the sum of acetate, propionate and butyrate, was similar for F1 and F2 (107 and 101 mM, respectively). The bifidobacteria counts also increased during the incubation time for both OS fractions.